Effects of Funding Allocation for Safe Routes to School Programs on Active Commuting to School and Related Behavioral, Knowledge, and Psychosocial Outcomes: Results From the Texas Childhood Obesity Prevention Policy Evaluation (T-COPPE) Study. (January 2016) - Hoelscher, Deanna; Ory, Marcia; Dowdy, Diane; Miao, Jingang; Atteberry, Heather; Nichols, Donna; Evans, Alexandra; Menendez, Tiffni; Lee, Chanam; Wang, Suojin
Few controlled evaluations of Safe Routes to School (SRTS) initiatives have been conducted. The Texas Childhood Obesity Prevention Policy Evaluation (T-COPPE) study included three conditions: schools awarded infrastructure (I) projects ( n = 23), schools awarded noninfrastructure (NI) projects ( n = 21), and matched comparison (C) schools ( n = 34). Fourth-grade children completed tallies to determine transport to/from schools. Serial cross-sectional surveys were collected from students and parents at baseline (2009) and follow-up (2012). Data were analyzed using mixed linear regression and growth curve models. Morning percent active commuting to school (ACS) in I and NI schools were higher than C schools ( p = .024, p = .013, respectively). Afternoon percent ACS in NI schools decreased more over time compared with C schools ( p = .009). I and NI school students had higher ACS self-efficacy; similar results were noted for parents in I schools. Policies that provide cost-reimbursement funding for SRTS achieve modest short-term ACS outcomes, with few differences between types of funding allocations.